Analisis Rasio Profitabilitas Pada CV Surya Indah Perkasa Di Tanjung Redeb - Dawami Buchori (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to determine whether the profitability ratio of CV Surya Indah Perkasa in Tanjung Redeb in 2020 has increased compared to 2019. The usefulness of the results of this study is as information for management to determine company policies related to increasing company profitability in the future. The analytical tool used in this research is the Profitability Ratio, namely Gross Profit Margin, Operating Profit Margin and Net Profit Margin. Based on the results of the study, it can be seen that the comparison of Profitability Ratios in CV Surya Indah Perkasa in Tanjung Redeb in 2020 with 2019 showing that Gross Profit margin in 2020 increased by 0.67%, Operating Profit Margin in 2020 increased by 3.39%, Net Profit Margin in 2020 increased by 2.97%. Based on these results, the proposed hypothesis is accepted.